Electronic resources: the Ohio state university EESEE project. Issue 2 (2003) - Graham, Petra L.; Notz, William I.; Pearl, Dennis K.; Stasny, Elizabeth A.
Abstract : Electronic resources aid in the teaching and learning of statistics by providing data that may be used interactively by teachers and students. By interacting with the data students are encouraged to discover knowledge and thereby gain a deeper understanding of statistical concepts. The Electronic Encyclopedia of Statistical Examples and Exercises (EESEE) is an electronic resource that includes over 80 'real-world' examples about the uses and abuses of statistics. These examples are drawn from published and printed media and the diverse range of subject-matter areas make it suitable for use in any statistics course.